Calcium-Mediated Oscillation in Membrane Potentials and Atrial-Triggered Activity in Atrial Cells of Casq2R33Q/R33Q Mutation Mice - Zhang, Jian-cheng; Wu, Hong-lin; Chen, Qian; Xie, Xiao-ting; Zou, Tian; Zhu, Chao; Dong, Ying; Xiang, Guo-jian; Ye, Lei; Li, Yang; Zhu, Peng-li (Frontiers in Physiology, 2018)
Aim We investigated the underlying mechanisms in atrial fibrillation (AF) associated with R33Q mutation and Ca2+-triggered activity. Methods and Results We examined AF susceptibility with intra-esophageal burst pacing in sarcoplasmic reticulum (SR) Ca2+ leak model Casq2 R33Q / R33Q (R33Q) mice. Atrial trigger appeared in R33Q mice but not WT mice (17.24%, 5/29 vs 0.00%, 0/32, P<0.05). AF was induced by 25-Hz pacing in R33Q mice (48.27%, 14/29 vs 6.25%, 2/32, P<0.01). Given 1.5 mg/kg isoproterenol (Iso), the incidences of AF were increased (65.51%, 19/29 vs 9.21%, 3/32, P<0.01). Electrophysiology experimentation and the recording of intracellular Ca2+ indicated that there were significant increases in Ca2+ sparks (5.24±0.75 100 μM-1.s-1 vs 0.29±0.04 100 μM-1.s-1, n=20, P<0.05), intracellular free Ca2+ (0.238±0.009 μM vs 0.172±0.006 μM, n=20, P<0.05), Ca2+ wave (11.74% vs 2.24%, n=20, P<0.05), transient inward current (ITi) (-0.56±0.02 pA/pF vs -0.42±0.01 pA/pF, n=10, P<0.05), and oscillation in membrane potentials (10.71%, 3/28 vs 4.16%, 1/24, P<0.05) in the R33Q group, but there was no significant difference in ICa-L. These effects were enhanced by Iso, and the inhibition of calmodulin-dependent protein kinase II (CaMKII) by 1 μM KN93 reversed the effects of Iso on Ca2+ sparks (5.01±0.66 100 μm-1.s-1 vs 11.33±1.63 100 μm-1.s-1, P<0.05), intracellular Ca2+ (0.245±0.005 μM vs 0.324±0.008 μM, P<0.05), Ca2+ wave (12.35% vs 17.83%, P<0.05), ITi (-0.61±0.02 pA/pF vs -0.78±0.03 pA/pF, n=10, P<0.05), and oscillation in membrane potential (17.85% 5/28 vs 32.17% 9/28, P<0.05). The reduction of RyR2 stable subunits (Casq2, triadin, and junctin) rather than RYR2 and the increase in CaMKII, phosphor-CaMKII, phosphor-RyR2 (Ser 2814), SERCA, and NCX1.1 was reflected in the R33Q group. Conclusions This study demonstrates that the increase in spontaneous calcium elevations (SCaEs) corresponds to ITi that may trigger oscillation in membrane potentials in the R33Q group, which increases the risk of AF. The occurrence of SCaE in R33Q atrial myocytes is due to dysfunction of RyR2 stable subunits, CaMKII hyperactivity and CaMKII-mediated RyR phosphorylation. An effective therapeutic strategy to intervene in Ca2+-induced AF associated with R33Q mutation may be to CaMKII inhibitors.